2013
DOI: 10.1128/aem.01142-13
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Transmission of Infectious Pancreatic Necrosis Virus from the Blue Mussel, Mytilus edulis, to Cohabitating Atlantic Salmon (Salmo salar) Smolts

Abstract: Integrated multitrophic aquaculture (IMTA) reduces the environmental impacts of commercial aquaculture systems by combining the cultivation of fed species with extractive species. Shellfish play a critical role in IMTA systems by filter-feeding particulate-bound organic nutrients. As bioaccumulating organisms, shellfish may also increase disease risk on farms by serving as reservoirs for important finfish pathogens such as infectious pancreatic necrosis virus (IPNV). The ability of the blue mussel (Mytilus edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Furthermore, experimental trials demonstrated that some bivalve mollusk species are able to accumulate and release viable viruses, including NNV (Molloy et al . 2013; Volpe et al . 2017; Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, experimental trials demonstrated that some bivalve mollusk species are able to accumulate and release viable viruses, including NNV (Molloy et al . 2013; Volpe et al . 2017; Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…The disease affected predominantly young salmonidsthe fried trout and Atlantic postsmolts (99). Clinical signs vary and include behavioral changes as spiral swimming, exophthalmos, open operculums bilaterally, anorexia (36).…”
Section: Epizootologymentioning
confidence: 99%
“…After an experimental infection, Molloy et al, demonstrated (2013) that Mytilus edulis has the ability to accumulate and transmit IPNV (99). Other researchers (102) observed viable virus in the digestive gland, muscle, gonads and rectum tissue at 333 day after the experimental injection of IPNV into the adductor muscle of scallop.…”
Section: Epizootologymentioning
confidence: 99%
“… 11 Interestingly, while currently unlisted in the Model Aquatic Health Code of the World Organization for Animal Health, the presence of IPNV is continuously being detected worldwide in both aquacultured 12 17 and wild fish, including several nonsalmonid species. 15 , 17 19 Apart from the fact that this virus is transmitted both vertically and horizontally, 20 , 21 fish that recover or are asymptomatically infected often become carriers of the virus throughout their lives, 11 , 22 contributing to its broad spread. Unfortunately, there is no therapy for this disease, so current protective measures are aimed at avoiding and alleviating its incidence.…”
Section: Introductionmentioning
confidence: 99%